2010
DOI: 10.1159/000288293
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Response of IgE Antibodies to Cellular Self-Antigens in Systemic Lupus Erythematosus

Abstract: Background: Systemic lupus erythematosus (SLE) patients may exhibit high total IgE and antinuclear IgE antibodies (ANA-IgE). Here, we investigated the specificity of ANA-IgE in SLE patients and the involvement of cytokines in this immune response. Methods: Sera from 92 SLE patients and 68 healthy controls were evaluated for the presence of antinuclear IgE antibodies by immunoperoxidase with HEp-2,000® cells and immunoblotting with IgG-depleted sera. Total IgE, IgE specific to allergens, and serum cytokine leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…Then, we found that IgE, especially autoreactive IgE, mediated basophil activation in SLE, based on the detection of abundant total IgE, autoreactive IgE, and the higher expression of the high-affinity receptor for IgE (FcεRIα) on basophils in patients with SLE, and in vitro experiments including isolated basophils cocultured with the serum of patients with SLE and PEG precipitation CIC (containing IgE). The prevalence of autoreactive IgE in SLE was also observed by others (23, 42, 43). …”
Section: Discussionsupporting
confidence: 81%
“…Then, we found that IgE, especially autoreactive IgE, mediated basophil activation in SLE, based on the detection of abundant total IgE, autoreactive IgE, and the higher expression of the high-affinity receptor for IgE (FcεRIα) on basophils in patients with SLE, and in vitro experiments including isolated basophils cocultured with the serum of patients with SLE and PEG precipitation CIC (containing IgE). The prevalence of autoreactive IgE in SLE was also observed by others (23, 42, 43). …”
Section: Discussionsupporting
confidence: 81%
“…Although the presence of IgE in different autoimmune disease, including T1D, has been reported [2][3][4][5][6][7]32,33] the potential contribution to the pathogenesis in the different diseases is still to be clarified. In this study, we have explored the role of IgE in a T1D model, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoglobulin IgE that is unanimously associated with allergy has also been shown to play a role in autoimmune diseases, a concept referred to as autoallergy [1]. Patients with autoimmune disease such as systemic lupus erythematosus [2,3] that display IgE autoantibodies have poor disease prognosis. Moreover, in several other autoimmune diseases, including rheumatoid arthritis [4], autoimmune thyroiditis [5], bullous pemphigoid [6] and T1D, presence of autoantigen specific IgE has been established [7].…”
Section: Introductionmentioning
confidence: 99%
“…The overall relevance of our initial report [46] describing a role for autoreactive IgE in SLE onset and progression was questioned [48], based on previous studies demonstrating that approximately only 30% of human SLE subjects had detectable levels of autoreactive IgE [49]. This percentage was determined primarily on the detection of dsDNA IgE, which similar to dsDNA IgG showed a highly significant association with disease parameters.…”
Section: Prevalence Of Autoreactive Ige In Sle and Its Diease Associamentioning
confidence: 99%